Association between Body Mass Index and Gastroesophageal Reflux Symptoms in Nepalese Adult Population. A Single Centered Hospital Based Study - Kasyap, Akhilesh Kumar; Sah, Shiv Kumar; Chaudhary, Sitaram; Shrestha, Ramila; Shrestha, Dinesh (Journal of College of Medical Sciences-Nepal, 2015)
Background & Objectives: Gastroesophageal reflux disease (GERD) is a common disorder, and studies have reported inconsistent association between high BMI and its elevated risk of GERD symptoms. The aim of the present study was to estimate the strength of the association between body mass index and reflux symptoms in Nepalese adults. Materials & Methods: This was a cross-sectional study conducted at National Academy of Medical Science, Bir Hospital, Kathmandu, Nepal. All patients of age 18 years or above who underwent endoscopy and diagnosed to have esophagitis were recruited for the analysis. Symptoms were identified by using a self-administered validated questionnaire regarding GERD that identify the onset for GERD symptoms and grade the frequency and severity of symptoms experienced over a period of one year. BMI data, the cut off points were based on the WHO classification of overweight and obesity. A BMI value ?25–30 represents overweight and BMI >30 indicates obesity. A BMI value <25 is considered as normal. Severity of erosive esophagitis was graded according to the Los Angeles classification. Results: The Among 127 enrolled esophagitis subjects, about 43% were under 20 BMI, 43% overweight and about 24% were obese. Obesity measured by BMI revealed no significant association among age, sex, smoker, alcoholics, hernia and severity grade of esophagitis (p>0.05). Ages with various categories (18-40, >40-60,>60) were significantly associated with the GERD symptoms (P=0.021). We categorize BMI in three categories. A BMI value < 25 (normal), ?25–30 (overweight), and BMI >30 (obesity). Categorical analysis of BMI with GERD symptoms confirmed the absence of any tendency towards an association (p>0.05). Conclusion: The tendency of reflux symptoms towards BMI is null, and weight reduction may not be the adequate justifiable for the symptoms therapy. JCMS Nepal. 2015; 11(2):23-26